ACCESSING THE IMPACT OF INFRASTRUCTURE ON INDUSTRIAL DEVELOPMENT AND TECHNOLOGICAL INNOVATIONS; EVIDENCE FROM PAKISTAN - Ali, Hina; Shaukat, Pinky; Aisha, Zinaz; Batool, Sahar (The journal of contemporary issues in business and government, 2022)
This study aims at the active examination of the strength of accessing the impact of infrastructure on industrial growth and technological innovations in Pakistan, by using annual time series data is taken from the period 1996 to 2020. The study uses ADF for unit root and ARDL for empirical estimations. Several works have been done for different variables across the world but this work is only done for the developing country Pakistan. Positive results have been found among industry including construction value added, medium of high tech exports and research and development with Gross fix capital formation in long run but renewable electricity output is not given significant results for Pakistan’s gross fix capital formation. The study reveals that IVA, RD_EX & MHTE thrice factors are essential contributors to infrastructure. Policy implications are a vital essence for the infrastructure of Pakistan, here are some policy suggestions for the Pakistani government. To strengthen infrastructure by new construct roads, modernized ways of transportation and innovative machinery installation. The government may take action with legislative measures according to the country’s welfare on China Pakistan Economic Corridor; secure investment friendly environment, political stability which can strengthen the economy, construction of modern transportation networks as well as several energy projects backward province KPK and Pakistan.